1983
DOI: 10.1111/j.2044-8341.1983.tb01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐modelling and weight control

Abstract: This study investigated the use of self-modelling in the treatment of obesity or overweight. Thirty-two females enrolled in a private slimming club volunteered to participate in this study which was conducted over a period of 10 weeks. The experimental and control groups were similar as far as their pre-treatment mean weights and desired mean weights were concerned. Analysis of the data indicated that towards the end of the study the experimental group lost significantly more weight than the control groups. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…( 2002 ), Law and Ste-Marie ( 2005 ), Lonnecker et al. ( 1994 ), Meharg and Lipsker ( 1991 ), Meharg and Woltersdorf ( 1990 ), Owusu-Bempah and Howitt ( 1983 , 1985 ), Possell et al. ( 1999 ), Ram and McCullagh ( 2003 ), Reamer et al.…”
Section: Kernel Definition Derivation and Examplesmentioning
confidence: 99%
“…( 2002 ), Law and Ste-Marie ( 2005 ), Lonnecker et al. ( 1994 ), Meharg and Lipsker ( 1991 ), Meharg and Woltersdorf ( 1990 ), Owusu-Bempah and Howitt ( 1983 , 1985 ), Possell et al. ( 1999 ), Ram and McCullagh ( 2003 ), Reamer et al.…”
Section: Kernel Definition Derivation and Examplesmentioning
confidence: 99%
“…It would be beneficial to investigate ethnicity, and MRM instead of race, as this would allow individuals to self-describe their ethnic background (Solomos & Collins, 2010). This would also allow for detecting ethnic differences if any were present (Connelly et al, 2016;Kashima & Gelfand, 2012) and contribute to ensuring that ethnic groups are sufficiently represented within research (Owusu-Bempah & Howitt, 2000;Redwood & Gill, 2013). Notably, the review was open to primary studies from Wales; however, none were found.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Coloniality has shaped the core principles, theories, and methods in psychology. Critical thinkers who were responsible for the creation of modern psychology played a key role in implicitly offering philosophical and evidence-based research to argue the superiority of the Anglo-Saxon race (Bhatia, 2002; Kessi, 2017; Owusu-Bempah & Howitt, 2000). Although it has been widely publicized, it bears repetition that American psychology produces research findings about psychological functions based on 5% of the world’s people on behalf of all the rest (Arendt, 2008).…”
Section: Western Psychology and The Global Southmentioning
confidence: 99%